Brain-based communication disorders - LaPointe, Leonard L.; Murdoch, B. E., 1950-; Stierwalt, Julie A. G. (Plural Pub., 2010)
Introduces the reader to the major clinically recognized types of acquired speech/language, cognitive, and swallowing disorders encountered by clinicians working with child and adult neurological cases.